Soil Contamination Current Consequences and Further Solutions - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This edited book, Soil Contamination - Current Consequences and Further Solutions, is intended to provide an overview on the different environmental consequences of our anthropogenic activities, which has introduced a large number of xenobiotics that the soil cannot, or can only slower, decompose or degrade. We hope that this book will continue to meet the expectations and needs of all interested in diverse fields with expertise in soil science, health, toxicology, and other disciplines who contribute and share their findings to take this area forward for future investigations.